1993
DOI: 10.1177/095646249300400508
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron Usage in HIV Positive Patients: A Pilot Study on the Control of Nausea and Vomiting in Patients on High Dose Co-Trimoxazole for Pneumocystis Carinii Pneumonia

Abstract: This was an open, single centre study, to evaluate the safety and efficacy of ondansetron in the treatment of co-trimoxazole associated nausea and vomiting in AIDS patients. Sixteen patients presenting with their first episode of HIV-associated Pneumocystis carinii pneumonia (PCP) on high dose co-trimoxazole were given ondansetron 8 mg orally, every 8 h. Measurements were made from data recorded by each patient on diary cards. In this study 11 out of 16 (69%) patients on ondansetron experienced good control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A small-scale study evaluating the efficacy of zofran for patients on high-dose bactrim for Pneumocystis carinii pneumonia (PCP) was conducted by Gompels et al in 1993. 29 The results indicated that 50% (8 of 16) experienced less vomiting during PCP treatment with zofran. While GI symptoms including nausea and vomiting have been found at levels similar to those reported for cancer patients, 30 management could prove to be quite different.…”
Section: Discussionmentioning
confidence: 96%
“…A small-scale study evaluating the efficacy of zofran for patients on high-dose bactrim for Pneumocystis carinii pneumonia (PCP) was conducted by Gompels et al in 1993. 29 The results indicated that 50% (8 of 16) experienced less vomiting during PCP treatment with zofran. While GI symptoms including nausea and vomiting have been found at levels similar to those reported for cancer patients, 30 management could prove to be quite different.…”
Section: Discussionmentioning
confidence: 96%